2006
DOI: 10.1159/000096079
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Serum Skin Test for Autoantibodies Is Associated with Airway Hyperresponsiveness in Patients with Asthma

Abstract: Background: Autoimmune diseases have been implicated as a cause of intrinsic asthma; however, there is little data on the role of autoimmunity in the pathogenesis of asthma. Objective: The purpose of this study was to investigate circulating functional autoantibodies against the high-affinity IgE receptor FcΕRI or IgE in patients with asthma. Methods: Twenty-eight patients with asthma and 19 control subjects were included. All subjects were skin tested with autologous serum to assess for the potential presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
3
6
0
2
Order By: Relevance
“…Early reports analyzing autoimmune background of allergic diseases show the presence of autoantibodies against IgE and/or FcɛR1α in allergic disorders, like chronic idiopathic urticarial and asthma . We also observed significantly high FcɛR1α antibodies in the study group.…”
Section: Discussionsupporting
confidence: 71%
“…Early reports analyzing autoimmune background of allergic diseases show the presence of autoantibodies against IgE and/or FcɛR1α in allergic disorders, like chronic idiopathic urticarial and asthma . We also observed significantly high FcɛR1α antibodies in the study group.…”
Section: Discussionsupporting
confidence: 71%
“…First, it was found that patients with nonallergic asthma frequently score positive on the autologous serum skin test (ASST), suggesting the presence of circulating histamine‐releasing factors in this disease (27), a finding that confirms pioneering observations by a Swedish doctor who carried out experiments with the so‐called autoserum test as long as 50 years ago (28). This observation was further analyzed by other researchers who showed that in patients with asthma, a positive ASST is associated with an increase in bronchial hyper‐responsiveness (29). Moreover, bronchial hyper‐responsiveness, which is a hallmark of asthma, is a frequent finding in patients with CU (30).…”
mentioning
confidence: 84%
“…Ogólne doświad czenia, w tym członków panelu, są takie, że u zdro wych osób z grupy kontrolnej i u pacjentów bez objawów PPS wynik ASST nigdy nie jest dodatni, a zatem nie stwierdza się reakcji miejscowej zdefi niowanej jako powstanie zapalnego bąbla o rumie niowym zabarwieniu [48][49][50][51][52][53][54][55][56][57][58][59][60]. W przeciwieństwie do większości wcześniej opublikowanych badań, niektóre prace wykazują relatywnie wysoki odse tek dodatniej reakcji w ASST u chorych z alergicz nymi lub niealergicznymi objawami ze strony ukła du oddechowego, wynoszący 30-50% u dorosłych pacjentów i aż do 80% w populacji dziecięcej [53][54][55][56]61]. W dwóch z tych badań u 40-45% zdrowych osób także uzyskano dodatni wynik ASST, choć jako kryterium wyniku dodatniego zostały przyjęte dane zatwierdzone tylko dla pokrzywki przewle kłej.…”
unclassified